Does the time of isolation need to be re-evaluated in prisoners with tuberculosis? (2012)
ABSTRACT: Background: According to WHO, CDC, IDSA and ATS guidelines, patients with pulmonary tuberculosis (Tb) can be considered as non infectious when: 1) they are receiving multiple drugs for 2 to 3 weeks; 2) there is an improvement in clinical condition; 3) the likelihood of MDR-Tb is very small. Objective: To determine the time for sputum reversion since the start of anti-Tb treatment in prisoners from four jails in Medellin and Bucaramanga, Colombia between May 2010 to April 2011. Methods: Prospective cohort study. All prisoners diagnosed with Tb by sputum smear or culture were followed for two years: monthly for the first six months after the start of treatment, bimonthly the next six months, and quarterly the second year. During follow-up, we took two spontaneous and one induced sputum samples for auramine-rodhamine stain, and cultures in thin layer agar, Löwestein-Jensen and MGIT for the both first samples. We did time to event analysis. Results: We could follow 45 of 47 positive patients (one was transferred to another jail and one Tb-related death). The median for sputum smear reversion was 33 days (IQR: 31-60), and for culture was 55 days (IQR: 32-68). 90% of the patients had sputum smear and culture negative at 102 days. The time for sputum to become negative by culture had a positive correlation with the sputum grade at the moment of diagnosis: negative smear with positive culture= median 31.5 days, smear with 1+ = 58.5 days, smear 2+ = 62 days, and smear 3+ = 65 days (p value = 0.007). Conclusion: After starting treatment the reversion of cultures took two or more months in ≥50% cases. That is forcing us to rethink the recommendations about the isolation of patients with pulmonary Tb in prisons, and suggests the need to use mycobacterial cultures on sputum to follow-up those patients.